Plasmonic Modes of Metamaterial-Based Slot Waveguides. (1st August 2012) - Rukhlenko, Ivan D.; Premaratne, Malin; Agrawal, Govind P.
Abstract : Most metamaterials exhibit pronounced anisotropic properties that are crucial for the understanding of their superior optical behavior, especially when they are integrated into the structure of a plasmonic waveguide. In this paper, we analytically solve the dispersion relation for a slot plasmonic waveguide filled with an anisotropic-stratified metamaterial and reveal that it supports two modes featuring relatively long propagation lengths in the limit of vanishing slot thickness. We classify these modes according to their physical origin and study the variation of their dispersion properties with material parameters.